Sinergisitas Pencapaian Target Pasar Produk Tabungan Haji Di Bank Syariah - Rahmayati , (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2019)
This research was conducted to find out how Islamic banks take steps that synergize in maximizing the achievement of Hajj savings products in the wider community. This research method is carried out by descriptive qualitative analysis using secondary data which is sourced from the supporting literature of this study and then analyzed in combination between theory and practice. Based on the results of the study that to maximize the synergy of achieving Hajj savings products in Islamic banks, Islamic banks carry out various marketing strategies, namely individuals, groups, community organizations and continue to make efforts to educate and socialize the importance of saving hajj savings from the start.